2019
DOI: 10.1177/0269215519853874
|View full text |Cite
|
Sign up to set email alerts
|

Training family to assist with physiotherapy for older people transitioning from hospital to the community: a pilot randomized controlled trial

Abstract: Objective: To investigate the safety and effectiveness of augmenting physiotherapy with family-assisted therapy, to inform a future, fully powered trial. Design: Parallel pilot randomized controlled trial. Setting: Transition Care Program. Participants: Thirty-five older adults with multimorbidity, recently hospitalized, with a mean age of 84.1 years (SD = 6.1 years) and mean Modified Barthel Index of 67.8 units (SD = 19.2 units), and 40 family members. Interventions: The control group ( n = 18) received usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Any disagreement was resolved through consensus following review by a third researcher (AMH). Three corresponding authors were contacted for additional information regarding their studies (Lawler et al, 2019;Morita et al, 2018;Parker et al, 2015).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Any disagreement was resolved through consensus following review by a third researcher (AMH). Three corresponding authors were contacted for additional information regarding their studies (Lawler et al, 2019;Morita et al, 2018;Parker et al, 2015).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…The search identified 7,205 studies (see Figure S1). A total of 21 studies (Abrahamsen et al, 2014(Abrahamsen et al, , 2016Chen et al, 2002;Dejong et al, 2009;Fiorini et al, 2013;Galizia et al, 2018;Gustavson et al, 2019;Herfjord et al, 2014;Hong et al, 2019;Jette et al, 2004;Jung et al, 2016;Lawler et al, 2019;Lenze et al, 2012Lenze et al, , 2019Leung et al, 2016;Mallinson et al, 2014;Millar et al, 2017;Morita et al, 2018;O'Brien & Zhang, 2018;Parker et al, 2015;Zhang et al, 2019) enrolling 1,206,769 participants were included. Characteristics of included studies are summarised in Table S1 (Appendix S1).…”
Section: Study Selectionmentioning
confidence: 99%
“…The cohort's levels of independence in ADL improved significantly and above a MCID through undertaking facility-based TCP. Improvement in ADL has been shown to vary across TCP settings with a range of between −9.26 points to 28 points ( 6 , 27 , 28 ). This could be due to differences in therapy duration, type of rehabilitation provided or the number of rehabilitation staff available, as suggested by a previous study that reported higher staff ratios were a significant predictor of functional improvement ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Physiotherapy has great potential to improve ICU care in low-resource settings because it requires no advanced equipment and can be provided by family members. 20 We cannot ignore obstacles to quality ICU care. For both patients a diagnosis of GBS was reached with lower levels of Brighton diagnostic certainty than are standard in more resourced-settings.…”
Section: Discussionmentioning
confidence: 99%
“…17–19 Physiotherapy has great potential to improve ICU care in low-resource settings because it requires no advanced equipment and can be provided by family members. 20…”
Section: Discussionmentioning
confidence: 99%